TRANSFORMASI DIGITAL DALAM MANAJEMEN MUTU TERPADU: STUDI KEBIJAKAN PAPERLESS DI PERGURUAN TINGGI - Muhammad Aulia Rahman; Ahmad Ridani; Muhlis; Fatima Azzahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the paperless campus policy within the perspective of Total Quality Management (TQM) in higher education. The research focuses on how document digitalization and administrative services can enhance efficiency, transparency, student satisfaction, and support environmental sustainability agendas. A qualitative descriptive method was employed, using interviews, observations, and document studies, with data analyzed through Miles & Huberman’s interactive model. The findings reveal that the paperless policy accelerates bureaucracy, strengthens accountability, improves student satisfaction, supports the principle of continuous improvement in TQM, and enhances the image and competitiveness of universities in the digital era. Therefore, paperless can be considered a comprehensive strategy that integrates administrative efficiency, sustainable quality culture, and commitment to environmental sustainability.